Small logging roads do not restrict movements of forest rats in Bornean logged forests - Heon,SP; Chapman,PM; Bernard,H; Ewers,RM (Biotropica, 2019)
Selective logging is driving the proliferation of roads throughout tropical rain forests, particularly narrow, unpaved logging roads. However, little is known about the extent of road edge effects or their influence on the movements of tropical understory animal species. Here, we used forest rats to address the following questions: (a) Does the occupancy of rats differ from road edges to forest interior within logged forests? (b) Do roads inhibit the movements of rats within these forests? We established trapping grids along a road edgetoforest interior gradient at four roads and in three control sites within a logged forest in Sabah, Malaysia. To quantify the probability of road crossing, rats were captured, translocated across a road, and then recaptured on subsequent nights. We caught 216 individuals of eight species on 3,024 trap nights. Rat occupancy did not differ across the gradient from road edge to interior, and 48 percent of the 105 translocated individuals crossed the roads and were recaptured. This proportion was not significantly different from that of rats returning in control sites (38% of 60 individuals), suggesting that small roads were not barriers to rat movements within logged forests. Subadults were significantly more likely to return from translocation than adults in both road and control sites. Our results are encouraging for the ecology of small mammal communities in heavily logged forests, because small logging roads do not restrict the movements of rats and therefore are unlikely to create an edge effect or influence habitat selection.